See Inside Planet Earth : With Over 80 Flaps to Lift - Daynes, Katie and Allen, Peter (London Usborne, 2008)
Includes double page spreads on mountains, deserts, the oceans, the atmosphere and icy landscapes such as Antarctica, each one with flaps to lift to reveal scientific and natural history information. This title contains a feature on how climate change is affecting our planet, and what can be done to reduce its effects.
Include Color Illustrations
Keywords: Earth (Planet) -- Earth sciences -- Toy and movable books